The relevancy of paracetamol and breastfeeding post infant vaccination: A systematic review - Suleiman, Nurain; Shamsudin, Siti Hadijah; Mohd Rus, Razman; Draman, Samsul; Mohd Taib, Mai Nurul Ashikin (MDPI, 2018)
Paracetamol may be used as an antipyretic agent for the treatment of fever, as well as an analgesic in the treatment of mild to moderate pain post-vaccination in infants. The use of paracetamol during fever may be or may not be recommended since it may alter the natural human body immune response, although it may reduce pain.